2002
DOI: 10.1016/s0304-3959(02)00242-7
|View full text |Cite
|
Sign up to set email alerts
|

Increases in the phosphorylation of cyclic AMP response element binding protein (CREB) and decreases in the content of calcineurin accompany thermal hyperalgesia following chronic constriction injury in rats

Abstract: Plasticity in the spinal dorsal horn may underlie the development of chronic pain following peripheral nerve injury or inflammation. In this study, we examined whether chronic constriction injury of the sciatic nerve was associated with changes in the immunoreactive content of cyclic AMP response element binding protein (CREB), protein kinase A (PKA), and calcineurin Aalpha and Abeta in the spinal dorsal horn. In animals exhibiting thermal hyperalgesia as a behavioral sign of neuropathic pain 7 days after loos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
74
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 19 publications
10
74
0
3
Order By: Relevance
“…As in other models of neuropathy (Ma and Quirion, 2001;Miletic et al, 2002;Song et al, 2005;Crown et al, 2006), the expression of the phosphorylated form of the CREB transcription factor significantly increased in the ipsilateral dorsal horn of SNL animals (Fig. 9, SNL, black bars), both in superficial and deep laminae (respectively ϩ21.0 Ϯ 2.8% and ϩ21.4 Ϯ 2.0% compared to contralateral dorsal horn).…”
Section: Ca V 12-dependent Gene Activationsupporting
confidence: 75%
“…As in other models of neuropathy (Ma and Quirion, 2001;Miletic et al, 2002;Song et al, 2005;Crown et al, 2006), the expression of the phosphorylated form of the CREB transcription factor significantly increased in the ipsilateral dorsal horn of SNL animals (Fig. 9, SNL, black bars), both in superficial and deep laminae (respectively ϩ21.0 Ϯ 2.8% and ϩ21.4 Ϯ 2.0% compared to contralateral dorsal horn).…”
Section: Ca V 12-dependent Gene Activationsupporting
confidence: 75%
“…19,23,24 Those rats who suffered from neuropathic pain demonstrated a similar phenomenon. 12,25 In contrast, Miletic et al reported that there were no differences in CREB content between control and study animals. 25 In fact, the effect of adenylate cyclase inhibitor on inflammatory response remains a topic for investigation.…”
Section: Discussionmentioning
confidence: 91%
“…A ativação de PKR por estímulos extracelulares ocorre, principalmente, pelos receptores da família TLR (Toll-like receptor) através da ligação com RNAds, lipopolisacarídeo (LPS), e peptídeoglicanos (Mannion et al, 1999;Miletic, Hanson e Miletic, 2004;Miletic, Hanson, Savagian, et al, 2004) desempenhando, assim, uma ação preponderante na ativação da resposta imune inata (Mcguire et al, 1997;Mantyh et al, 2002;Miletic et al, 2002;Miyabe e Miletic, 2005). Sabemos, hoje, que PKR sinaliza também em resposta, fatores de crescimento, como o Fator de Crescimento Derivado de Plaquetas (PDGF, platelet-derived gowth factor) e citocinas como o interferon, interleucina-1 (IL-1) e o Fator de necrose tumoral-α (TNF-α, tumor necrosis factor) (Mcguire et al, 1997;Mantyh et al, 2002;Miletic et al, 2002;Miyabe e Miletic, 2005).…”
Section: Ativação Da Pkrunclassified
“…Sabemos, hoje, que PKR sinaliza também em resposta, fatores de crescimento, como o Fator de Crescimento Derivado de Plaquetas (PDGF, platelet-derived gowth factor) e citocinas como o interferon, interleucina-1 (IL-1) e o Fator de necrose tumoral-α (TNF-α, tumor necrosis factor) (Mcguire et al, 1997;Mantyh et al, 2002;Miletic et al, 2002;Miyabe e Miletic, 2005).…”
Section: Ativação Da Pkrunclassified
See 1 more Smart Citation